The Phenomenon of Citizen Journalism in National Football in Liga 1 Competition - Fadli Muhammad Athalarik (CV. Publikasi Indonesia, 2024)
The football industry in Indonesia is currently starting to develop well, both in terms of owners, management, coaches, players, and supporters. This industry is slowly making many people want to speak out about the issues that occur in football, especially on social media today. One proof of how many people are starting to speak out is the existence of citizen journalism in Indonesian football today. This research aims to find out how citizen journalism is implemented in the League 1 Competition in Indonesian Football. This research uses qualitative research with descriptive methods, as well as collecting data through secondary data through documentation and interviews from social media such as YouTube, Instagram, TikTok, and so on. The results of this research show that there are several ways for the community to implement it, namely the first is Participatory Citizen Journalism using the community to write their personal opinions in the National Media. Second, Citizen Journalism by writing content or producing visual, audio, or even audio-visual content related to specific content topics. Third, News-Media Watchdog Citizen Journalists, namely the media as watchdogs monitor and evaluate the current performance in the football industry through media such as YouTube and Spotify. Lastly, Community Citizen Journalism is how communities, in this case supporters, have their media to inform about their favorite team or voice something related to their favorite team, such as Simamaung.com (Persib Bandung), Jak Online (Persija Jakarta), EmosiJiwaku.com (Persebaya Surabaya).